Population structure, dispersion patterns and genetic diversity of two major invasive and commensal zoonotic disease hosts (Rattus norvegicus and Rattus tanezumi) from the southeastern coast of China - Li, Jiaqiao; Huang, Enjiong; Wu, Yifan; Zhu, Changqiang; Li, Wenhao; Ai, Lele; Xie, Qinghua; Tian, Zhi; Zhong, Weiwen; Sun, Gang; Zhang, Lingling; Tan, Weilong (Frontiers in Genetics, 2024)
Background: The invasive brownrat (Rattus norvegicus) and the Oriental rats (R. tanezumi) are common commensal murid that are important hosts for rodent-borne diseases in southeast Asia. Understanding their population structure and genetic diversity is essential to uncover their invasion biology and distribution dynamics that are essential for controlling rodent-borne diseases. Methods：A total of 103 R. norvegicus and 85 R. tanezumi were collected from 13 and 9 coastal areas of six provincial monitoring sentinel sites, respectivelyto assess patterns in their microsatellite loci and their mitochondrial coxl gene region. Results: Eleven sampled populations of R. norvegicus were divided into two major clusters by region. The observed heterozygosity (Ho) values of all regional populations were smaller than expected genetic diversity (He) values and deviated from Hardy-Weinberg equilibrium (HWE). Nine sample populations of R. tanezumi were divided into three clusters; two that included sample from Hainan and Fujian provinces, and one that included samples from the other provinces and cities. The genetic diversity of R. tanezumi was highest in samples from Jiangsu and Guangdong provinces. Conclusions: The data in this paper confirm the two invasive rodent species from the southeastern coastal region of China may have relied on maritime transport to spread from the southern region of China to the Yangtze River basin. Rattus tanezumi may then hanve migrated unidirectionally, along the southeastern provinces of China towards the north, while R. norvegicus spread in a complex and multidirectional manner in Hainan, Fujian, Zhejiang and Jiangsu Provinces of the country.